2011
DOI: 10.3892/ol.2011.385
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol induces JNK-dependent apoptosis in glioblastoma cells

Abstract: Abstract. Estrogens exert multiple regulatory actions on cellular events in a variety of tissues including the brain. In the present study, the signaling mechanisms of the concentration-dependent effects of 17-β-estradiol (estradiol) on glioblastoma cells were investigated. Cell viability was evaluated by the trypan blue exclusion assay. Cell growth and kinase activities were evaluated by immunocytochemistry and Western blotting. The results showed that high concentrations of estradiol inhibit growth and induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
4
16
0
Order By: Relevance
“…To achieve this, the effect of E2 on the viability of glioblastoma cells was initially assessed. A previous study had indicated that E2 activates the c-Jun N-terminal kinase/c-Jun signaling cascade and inhibits the growth of rat C6 glioblastoma and human T98G glioblastoma cells, with an half maximal inhibitory concentration of 3.5 µM (34). The results of the present study indicated that E2 treatment for 24 h reduced the viability of C6 and U87-MG cells to 71.33 and 59.28%, respectively.…”
Section: Discussionsupporting
confidence: 58%
“…To achieve this, the effect of E2 on the viability of glioblastoma cells was initially assessed. A previous study had indicated that E2 activates the c-Jun N-terminal kinase/c-Jun signaling cascade and inhibits the growth of rat C6 glioblastoma and human T98G glioblastoma cells, with an half maximal inhibitory concentration of 3.5 µM (34). The results of the present study indicated that E2 treatment for 24 h reduced the viability of C6 and U87-MG cells to 71.33 and 59.28%, respectively.…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies showed that high concentrations of estradiol, under low growth-stimulated conditions, inhibit cell proliferation and increase apoptosis in ER-positive breast cancer cells through the sustained activation of the JNK pathway [12,22]. ese findings emphasize the basis for the antitumor effects of high-dose estrogen therapy in postmenopausal women approximately 40 years ago [20].…”
Section: Discussionmentioning
confidence: 80%
“…The top-ranked drugs from our approach include targeted cancer therapy, such as tamoxifen, cytotoxic cancer therapy, such as etoposide, and non-cancer drugs with supporting evidence from previous studies. For example, among the top ten predicted drugs, estradiol is a form of estrogen and induces JNK-dependent apoptosis in human GBM and rat glioma cells [5]; arsenic trioxide has demonstrated preclinical evidence in treating infiltrating astrocytomas [9]; and imipramine, an antidepressant and nerve pain medication, targets on the autophagic regulatory circuitry in gliomas and increased autophagy in tumor-bearing animals [28]. …”
Section: Resultsmentioning
confidence: 99%